ANALISIS STRATEGI PELAKSANAAN PROGRAM RUMAH SAKIT TANPA DINDING (HOSPITAL WITHOUT WALLS) DI RSJD DR. AMINO GONDOHUTOMO PROVINSI JAWA TENGAH MENGGUNAKAN MATRIKS SWOT DAN QSPM - Cika Hanjani Pratiwi; Sutopo Patria Jati; Septo Pawelas Arso (Jurnal Kesehatan Masyarakat (Undip), 2021)
The variety of health problems in Central Java is that there are not yet optimal public health efforts held in primary healthfacilities, like as Puskesmas in promotive and preventive services. According to this problem, the Governor of Central Java for the 2018-2023 period launched an innovation program, namely the Hospital Without Walls (HWW)  which aims to strengthen public health efforts and empower the community. RSJD Dr. Amino Gondohutomo is one of the seven provincial hospitals that implemented the HWW. In two years of implementing HWW, an evaluation and improvement strategy is needed. So the purpose of this study is to describe and analyze strategies in an effort to optimize the implementation of HWW. This research is a qualitative research using descriptive method through in-depth interviews, informants were selected based on purposive sampling technique. The main informants are the Director, Deputy Director of Services, Head of Medical Services, Manager of Patient Services, and Head of Planning and Education Division. Triangulation informants are the health promotion leader and members of the HWW coordinating team. The results showed that internal factors in the form of strengths and weaknesses, as well as external factors such as opportunities and threats in the implementation of the HWW. The implementation of the HWW is in quadrant 3, which is a turn around strategy. Where this strategy minimizes internal weaknesses to take advantage of existing opportunities. Alternative strategies that can be implemented is to equate perceptions of understanding and positive mental attitudes for directors, managerial, and hospital staff.